Effects of physical activities on dementia‐related biomarkers: A systematic review of randomized controlled trials. Issue 1 (20th January 2021) - Moniruzzaman, Mohammad; Kadota, Aya; Akash, Maksudul Shadat; Pruitt, Patrick J; Miura, Katsuyuki; Albin, Roger; Dodge, Hiroko H.
Abstract: Introduction: Physical activities (PA) may lead to improved cognition in mild cognitive impairment (MCI), Alzheimer's disease (AD), and dementia. The mechanisms mediating potential PA effects are unknown. Assessment of PA effects on relevant biomarkers may provide insights into mechanisms underlying potential PA effects on cognition. Methods: We systematically reviewed randomized controlled trials (RCTs) that studied PA effects on biomarkers in MCI, AD, and dementia populations. We examined whether biological mechanisms were hypothesized to explain associations among PA, biomarkers, and cognitive functions. We used the PubMed database and searched for RCTs with PA until October 31, 2019. Results: Of 653 studies examining changes in biomarkers in PA trials, 18 studies met inclusion criteria for the present review. Some studies found favorable effects of PA on neurotrophic and inflammatory biomarkers. AD pathological markers were rarely investigated, with inconclusive results. Most studies were relatively small in sample size, of limited duration, and not all studies compared the changes in biomarkers between the control and experimental groups. Discussion: There is only limited use of potentially informative biomarkers in PA trials for MCI, AD, and dementia. Most studies did not examine the role of biomarkers to study associations between PA and cognitive functions in their analyses. Several potential biomarkers remain uninvestigated. Careful use of biomarkers may clarify mechanisms underlying PA effects on cognition. Our review serves as a useful resource for developing future PA RCTs aimed at improving cognitive functions in MCI, AD, and dementias.